The management and managers of the future in the context of the globalization of economic life - Ovidiu Andrei Cristian BUZOIANU; Cristina DIMA; Vicentiu MATEESCU; Ilinca Carina GOMBOS (Revista de Management Comparat International)
We notice that our society has been going through a series of radical transformations for some time that leave their mark in all areas of life: the accelerated pace of innovation through the development of technology, the digitalization of services, the economic changes that lead to the redistribution of the poles of well-being, competitiveness and opportunity among the workforce work, reducing the amount of available resources and increasing the struggle for the already existing ones, including in the labor market. These forces, which until now seemed to draw new patterns only at the macro, business level, are increasingly felt at the individual level as well. And this is how, in the midst of the digital revolution, managers are also challenged to continuous change. We are thus witnessing the emergence of a new type of manager, in which his role as a leader leaves the sphere of the discourses of capitalist organizations, entering also into the personal plane.